Thermoanalytical Study of the superconductor Compound Y0.85 Ho0.15 Ba2 Cu3 O7 - Dawood, Azhar Jawad (Al-Nahrain Journal of Science, 2013)
A ceramic superconductor compound Y0.85 Ho0.15 Ba2 Cu3 O7 was prepared by solid state reaction method in our laboratory. The thermo analytical behavior of the prepared compound in the range 20-1000 OC has been studied using DTA technique. Use has been made of the equations of Avrami and Arrhenuis to determine the most significant parameters of our compound, where we have introduced the data extracted from the DTA spectrum of our compound into the two equations. The outputs from the equations included important parameters such as the growth rate (k), kinetic of transformation (n) and the activation energy Ea, which was found equal to 0.72 eV.